2014
DOI: 10.3390/rs6010621
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Behavior of Lake Size-Distribution in a Thawing Permafrost Landscape in Northwestern Siberia

Abstract: Abstract:Arctic warming alters regional hydrological systems, as permafrost thaw increases active layer thickness and in turn alters the pathways of water flow through the landscape. Further, permafrost thaw may change the connectivity between deeper and shallower groundwater and surface water altering the terrestrial water balance and distribution. Thermokarst lakes and wetlands in the Arctic offer a window into such changes as these landscape elements depend on permafrost and are some of the most dynamic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 46 publications
1
43
0
2
Order By: Relevance
“…The dense stacking methodology, which utilizes all available imagery to compile a best composite image, can be problematic for evaluating long-term changes in streams and small lakes subject to seasonal fluctuations. For example, a given image composite with the majority of its images from spring and/or early summer might result in artificially inflated areas occupied by water due to snow-melt flooding [26][27][28]. To address this potential problem, the following water bodies were eliminated from the analysis following guidelines provided by Smith et al [24]: all rivers, streams, and lakes smaller than 40 ha, and lakes connected to river systems, as these are either highly sensitive to seasonality or ephemeral in nature compared to larger closed lakes [53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dense stacking methodology, which utilizes all available imagery to compile a best composite image, can be problematic for evaluating long-term changes in streams and small lakes subject to seasonal fluctuations. For example, a given image composite with the majority of its images from spring and/or early summer might result in artificially inflated areas occupied by water due to snow-melt flooding [26][27][28]. To address this potential problem, the following water bodies were eliminated from the analysis following guidelines provided by Smith et al [24]: all rivers, streams, and lakes smaller than 40 ha, and lakes connected to river systems, as these are either highly sensitive to seasonality or ephemeral in nature compared to larger closed lakes [53].…”
Section: Resultsmentioning
confidence: 99%
“…Changes in permafrost conditions can greatly affect surface hydrology (e.g., [24,[26][27][28]30]). Thaw propagation into ice-rich near-surface permafrost can be accompanied by ground subsidence (e.g., [60]) and/or formation or expansion of thermokarst depressions (e.g., [61]).…”
Section: Discussionmentioning
confidence: 99%
“…The overwhelming majority of these lakes are not connected to the rivers, being isolated water bodies, protected by an impermeable permafrost layer both from the bottom (frozen sand and silt), and from the border (frozen peat). Probably for these reasons, the on-going dynamics of thermokarst lake abundances and surface areas are not yet reflected in the hydrological balance of large rivers in Western Siberia [40,47]. The stock of dissolved components in lakes on the permafrost-affected WSL territory can be compared to that delivered by all rivers of the WSL from the same territory to the Arctic Ocean.…”
Section: Stock Of Doc and Metals In Thermokarst Lakes Of The Wslmentioning
confidence: 99%
“…Remote sensing studies of the permafrost zone of western Siberia demonstrated that the number of newly formed small thermokarst lakes (0.5-5 ha) over the past three decades exceeds, by a factor of 20, the number of large lakes which tend to disappear during the same period [46]. Recently, the dynamics of the number and surface area of thermokarst lakes in the discontinuous permafrost zone of western Siberia, over the period of 1973 to 2009, has been studied within the watersheds of the Nadym and Pur rivers [47]. According to these authors, the temporal evolution of large size (>10 ha) lakes, whose number constituted 78%-85% of all lakes, exhibited a variation within 10%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation